UNJUK KERJA METODE KLASIFIKASI SUPPORT VECTOR MACHINE (SVM) DENGAN LEARNING VECTOR QUANTIZATION (LVQ) PADA APLIKASI PENGENALAN WAJAH - Yustina Retno Wahyu Utami, Teguh Susyanto (STMIK Sinar Nusantara, 2015)
Face recognition techniques and classification methods have been proposed, but not many techniques that compare performance between methods. This research wants to analyze the performance of recognition. The method which are studied and compared are support vector machine and learning vector quantization. The result showed that the performance of the method, on the varied training number, LVQ method is better than SVM. In large number of classes, LVQ method is better than SVW.Keywords: classification, face recognition, LVQ, SVM